Automated Reasoning for Security Protocol Analysis and Issues in the Theory of Security Joint Workshop, ARSPA-WITS 2010, Paphos, Cyprus,March 27-28, 2010. Revised Selected Papers - Armando, Alessandro; Lowe, Gavin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the Joint Workshop on Automated Reasoning for Security Protocol Analysis and Issues in the Theory of Security held in Paphos, Cyprus, in March 2010.
Keywords: Computer science; Computer Communication Networks; Software engineering; Data encryption (Computer science).; Computer software; Computer Science; Data Encryption; Computer Communication Networks; Computers and Society; Algorithm Analysis and Problem Complexity; Software Engineering; Programming Languages, Compilers, Interpreters